2003
DOI: 10.1046/j.1469-1809.2003.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Element for the Lactase Persistence/ non‐persistence Polymorphism is Located in a 1 Mb Region of Linkage Disequilibrium in Europeans

Abstract: SummaryExpression of lactase in the intestine persists into adult life in some people and not others, and this is due to a cisacting regulatory polymorphism. Previous data indicated that a mutation leading to lactase persistence had occurred on the background of a 60 kb 11-site LCT haplotype known as A (Hollox et al. 2001). Recent studies reported a 100% correlation of lactase persistence with the presence of the T allele at a CT SNP at − 14 kb from LCT, in individuals of Finnish origin, suggesting that this S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
121
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 21 publications
(35 reference statements)
12
121
0
3
Order By: Relevance
“…As far as the discrepancy observed in one individual (30 years and of Sardinian descent) with a lactose normal absorption carrying a lactose non-persistent genotype is concerned, several explanations may account for this divergence: (a) the genetic switch of adult type hypolactasia in rare individuals might be postponed to later in life; (b) the association of lactase non-persistence with the C/T-13910 variant might be not absolute (Poulter et al, 2003); (c) the breath test could be falsely negative for unexplained reasons in a normal H2 producer. Indeed, it has been reported that two individuals from Naples carrying the C/C-13910 genotype had a high lactase activity determined by enzyme assay (Swallow, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…As far as the discrepancy observed in one individual (30 years and of Sardinian descent) with a lactose normal absorption carrying a lactose non-persistent genotype is concerned, several explanations may account for this divergence: (a) the genetic switch of adult type hypolactasia in rare individuals might be postponed to later in life; (b) the association of lactase non-persistence with the C/T-13910 variant might be not absolute (Poulter et al, 2003); (c) the breath test could be falsely negative for unexplained reasons in a normal H2 producer. Indeed, it has been reported that two individuals from Naples carrying the C/C-13910 genotype had a high lactase activity determined by enzyme assay (Swallow, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…8 Further to this, extensive linkage disequilibrium for 1 Mb across LCT has been reported in a North European population. 10 This work places the correlated allele on an extended common haplotype background and there is redundancy with respect to the genotyping of further variants associated with lactase persistence. Therefore, genotyping of the putatively causal C/T À13910 variant (rs4988235) will effectively capture the genetic variation highlighted by previous association studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, genotyping of the putatively causal C/T À13910 variant (rs4988235) will effectively capture the genetic variation highlighted by previous association studies. 8,10 The T allele of this single nucleotide polymorphism (SNP) is associated with lactase persistence and its prevalence has been shown to vary across Europe, being 70-80% in Northern European populations and 5 -10% in Southern European populations. 6 The geographic variation in the prevalence of lactase persistence raises the possibility that C/T À13910 may also vary geographically within a country such as Britain, as part of the north-south gradient seen across much of Europe.…”
Section: Introductionmentioning
confidence: 99%
“…These may lie, for example, in adjacent noncoding sequence that regulates transcription or translation. This suggestion should find favour among those advocating hunts for causative SNPs within regulatory regions, for example, King and Wilson 7 and Prokunina et al 8 The authors' final explanation is that lack of conservation may not rule out the functional importance of their diseaseassociated SNPs if these functions have been acquired only recently in primate evolution. Comparisons with more distantly related mammals might not show conservation if SNP sites have been evolving rapidly under adaptive pressures in our lineage.…”
mentioning
confidence: 99%